THE İMPACT OF VİOLENCE ON THE PROCESS OF SELF-ACTUALİZATİON: MAİN DİRECTİONS - Aygun, Karimli (Revista Gênero e Interdisciplinaridade, 2025)
The study was devoted to the study of the impact of violence on the process of self-actualization. The results of the study showed that there is a significant negative relationship between self-actualization and social anxiety. This relationship can present itself as an indicator of violence. The analysis of the conducted studies showed that there is a relationship between self-actualization and anxiety in early adulthood and children who were victims of violence in childhood. The study showed that it was possible to determine whether there were differences in the results regarding the relationship between self-actualization and general anxiety in various aspects. The results showed that the level of self-actualization of people who have been subjected to violence depends largely on their self-awareness, and this was unequivocally confirmed. Studies have shown that violence most often affects behavioral elements, the emotional and cognitive sphere, which makes it difficult for a person who is a victim of violence to self-actualize, and he cannot reveal his potential in the face of any trauma. The facts show that the facts of violence most affect the context of self-actualization. That is, the individual unknowingly directs himself in the direction that the subconscious takes him, under the influence of the trauma. That is, he is directed not in the direction dictated by abilities, but in the direction dictated by traumas.